SISTEM PENGENDALIAN INTERNAL DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN KAS DAN SETARA KAS PADA PT. KAWASAN INDUSTRI MEDAN (PERSERO) - Rat, Mohan (Universitas Muhammadiyah Tangerang, 2024)
The aim of this research is to examine how PT. Medan Industrial Estate manages cash and cash equivalents related to the internal control system. Whether internal control over the management of cash and cash equivalents has been implemented in accordance with the principles of Financial Accounting Standards (SAK) is the main concern of this research. Qualitative descriptive research is the research methodology used, that is, actual data is analyzed, processed, and research findings are explained. Research findings show that PT. Medan Industrial Estate's internal control over the management of cash and cash equivalents is effective and in line with the policies set by company management.